Ecological Economic Systems: concepts and research experiences (a proposed application for the Central Highland region) - Hai, Pham Hoang; Thinh, Nguyen An; Nhung, Nguyen Thu; Bac, Hoang; Phuong, Tran Thi Mai (Vietnam Journal of Earth Sciences, 2014)
The paper deals with the concepts and research experiences for resources and environmental assessment and building a capacity for establishing sustainable ecological economic systems. For the past several decades, some urgent problems have been emerged in the Central Highland region of Vietnam, such as poverty, conflicts between economic development and environment protection, the raising of natural hazards and its effects, and etc. It is therefore sustainable development is considered as the priority goal for both of this region and its four typical sub-regions, including plateaus of Da Lat, Pleiku and Dak Nong, and Cheo Reo - Phu Tuc lowland. For this study, we proposed some specific economic development models and ecological economic ones as well as followings: model for local key industrial production; Highlands-specific model for agro-forestry production and business; model for tourism and service development; model for sustainable agriculture business; model for sustainable development for the frontier post and borderland corridor economics for Central Highlands and some its key geographic areas. As the main result of this study, these specific types of ecological economic system which are proposed for future applying in this region could be played its roles as driving forces for promoting the sustainable development of this region in the new tendency.